Relationship between ambient light and glucose metabolism in healthy subjects - Hirofumi Hirakawa; Takeshi Terao; Koji Hatano; Kentaro Kohno; Nobuyoshi Ishii (BMC Neuroscience, 2018)
Abstract Background Given the reported inverse association between light and depressive mood, ambient light may also be associated with some of the brain regions in healthy subjects. The present study aims to investigate the effects of ambient light on glucose metabolism in the brain. We used the data of 28 healthy participants of the no intervention group from our previous randomized controlled trial and analyzed the association between ambient light and [18F]-FDG uptake in the brain. Results A whole brain analysis revealed a cluster of [18F]-FDG uptake that was significantly and inversely associated with log-transformed ambient light in the left culmen of the left cerebellum vermis. After adjustment for age, gender and serum melatonin levels, there remained a significant cluster of [18F]-FDG uptake with log-transformed ambient light in the left cerebellar vermis. Conclusions The present findings suggest that the uptake of [18F]-FDG is significantly and inversely associated with ambient light in the left cerebellar vermis in healthy subjects. The cerebellar vermis may be involved in mood suppression which may be alleviated by light exposure where glucose uptake and metabolism in this area are decreased. Trial Registration This study is a secondary analysis of the previous randomized study which was registered as UMIN000007537. Retrospectively registered (March 20th, 2012).